Endoscopic Radial Tunnel Release - Tun Hing Lui, M.B.B.S. (HK), F.R.C.S. (Edin); Ka Kin Cheung, M.B.B.S. (HK), F.R.C.S. (Edin); Amanda Mun Yee Slocum, M.B.B.S. (HK), F.R.C.S.Ed. (Orth); Kar Hei Lam, M.B.B.S. (HK) (Arthroscopy Techniques)
Compression neuropathies of the radial nerve at the radial tunnel include radial tunnel syndrome and posterior interosseous nerve syndrome. The potential 5 structures causing posterior interosseous nerve entrapment within the radial tunnel include the fibrous bands from the radiocapitellar joint, recurrent radial vessels (leash of Henry), leading medial proximal tendinous edge of the extensor carpi radialis brevis, fibrous proximal edge of the superficial head of supinator (arcade of Frohse), and distal border of the superficial supinator head. Surgical decompression is indicated if symptoms are refractory to nonoperative treatment. The purpose of this Technical Note is to describe the details of endoscopic radial tunnel release. This minimally invasive approach can release all the potential entrapment sites.